Physical activity education to prevent stunting and anemia in SDN Setiawarga - Oktaviani Prameswari Nur Gayatri; Adinda Athania (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Stunting is an important problem to solve because it has risks to human resource potential. It can even cause death in children. The impact caused by stunting on health in toddlers is that children have a smaller brain volume than healthy toddlers, underweight can also inhibit cognitive and motor development, and adults are susceptible to metabolic disorders. This service aims to provide an understanding to the Indonesian people so that they know the dangers of stunting, especially for students at SDN Setiawarga. Based on the results of the Survey Status Gizi Indonesia (SSGI), Indonesia was at twenty one point six percent in 2022; this figure is still considered high according to WHO, which targets stunting rates to be no more than twenty percent. This activity is implemented through offline socialization, presentations, and questions and answers. From the results of the socialization that has been carried out, it is hoped that it can improve the habits of SDN Setiawarga students, get them used to doing simple physical activities, and help them implement a healthy lifestyle in their daily lives.   Abstrak Stunting merupakan masalah yang penting untuk diselesaikan karena memiliki risiko dalam potensi sumber daya manusia. Hal tersebut bahkan dapat menyebabkan kematian pada anak. Dampak yang disebabkan oleh stunting dalam kesehatan pada balita berupa anak memiliki volume otak lebih kecil dibanding balita sehat, berat badan yang kurang juga dapat menghambat perkembangan kognitif dan motorik dan saat dewasa rentan mengalami gangguan metabolik. Pengabdian ini memiliki tujuan untuk memberikan pemahaman kepada masyarakat Indonesia agar masyarakat sadar akan bahaya stunting khususnya kepada para peserta didik di SDN Setiawarga. Di Indonesia sendiri berdasarkan hasil Survei Status Gizi Indonesia (SSGI) berada di angka dua puluh satu koma enam persen pada tahun 2022, angka ini masih dinilai tinggi menurut WHO yang menargetkan angka stunting untuk tidak lebih dari dua puluh persen. Metode pelaksanaan kegiatan ini melalui sosialisasi secara luring, presentasi dan juga tanya jawab. Dari hasil sosialiasi yang telah dilakukan, diharapkan dapat meningkatkan kebiasaan para peserta didk SDN Setiawarga untuk membiasakan diri melakukan aktivitas fisik sederhana dan menerapkan pola hidup sehat di kehidupan sehari-hari. Kata Kunci: anemia; aktivitas fisik; stunting